Dos crimes contra o Sistema Financeiro Nacional como expressão do Direito Penal simbólico no Brasil - Amanda Bastos Alves (2016)
The crises on the legitimacy of the instrumental functions of the criminal system is the central point of the discussions about the modern criminal law. It concerns a repressive, labelling, irational and inefficient instrument, incapable of solving the complex social questions that it intends to protect. One of these controversial areas of criminal protection is, in the context of Brazilian law, the National Finacial System. The crimes against the National Financial System, described on the law number 7.492/86, were created in a criminal politics context of criminalizing risks, carrying within the speech of stabilization of economic-finnacinal basis. However, it is necessary to argue the harmony of this specific criminal law with the requirements os incrimination and with the expressed purpose of protection of legally protect interests. This dissertation intends, therefore, to analyse the crimes of the law number 7.492/86, revealing its symbolic character of the criminal laws and its relation to a trend of expansion of criminal legislation oriented to the management of risks and to the administrativization of criminal law. As it will be demonstrated, part of these crimes exist in disagreement with the limits of the criminal power of the State and are an example of the symbolic criminal law in Brazil. Lastly, it will be examined the alternative solutions of contention of the irrational and symbolic expansion of contemporary criminal law.